Insulin receptor substrate 2 and FozO3a signaling are involved in E-Cadherin expression and transforming growth factor-β1-induced repression in kidney epithelial cells - HICKEY, FIONNUALA (My University, 2011)
Insulin receptor substrate (IRS) proteins comprise a family of adaptor molecules that integrate extracellular signals from insulin and other ligands to intracellular effectors such as phosphoinositide 3-kinase and mitogen activated protein kinase. The predominant forms of IRS protein in humans, IRS1 and IRS2, are widely expressed. Despite structural similarities, IRS1 and IRS2 display distinct signalling modalities, and mice lacking these proteins present with distinct phenotypes. Transforming growth factor (TGF)-b1 is the primary cytokine shown to induce epithelial–mesenchymal transition. Recent data have demonstrated a role for IRS1 in TGFb1-induced epithelial–mesenchymal transition in lung epithelial cells. In the present study, we report data showing that TGF-b1 signals via IRS2 in kidney epithelial cells. Small interfering RNA (siRNA)-mediated targeting of IRS2 increased E-cadherin expression, although it did not alter TGF-b1-mediated E-cadherin repression. Phosphorylation of the downstream target of IRS2 ⁄ Akt signalling, FoxO3a, was induced on Ser253 and, to a lesser extent, on Thr32. Transfection of FoxO3aThr32Ala mutant for 24 h greatly reduced FoxO3a phosphorylation on Ser253 but over-expression of FoxO3a Ser253Ala did not effect Thr32 phosphorylation, suggesting that a distinct order of phosphorylation of FoxO3a is required for physiological function in cells. Transfection of FoxO3a Ser253Ala mutant partially inhibited TGF-b1-mediated E-cadherin repression at 24 h. Taken together, these data highlight novel roles for IRS2 and FoxO3a in the regulation of kidney epithelial cells by E-cadherin.
PUBLISHED
Keywords: E-cadherin; FoxO transcription factor; insulin receptor substrate; kidney; transforming growth factor-beta